Green sheet for silicon nitride and silicon nitride substrate
Patent Information
- Application Number
- JP2024219735
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-12-15
AI Technical Summary
【0021】 本発明によると、外観不良や成形精度不良が少なく高い熱伝導率を示す窒化シリコンの焼結体を得ることができる窒化シリコン用グリーンシート、および、窒化シリコン基板を提供することができる。
Smart Images

Figure 2025026747000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon nitride green sheet containing silicon and a sintering aid, which is used as a precursor of a silicon nitride sintered body, and a silicon nitride substrate. [Background technology]
[0002] Silicon nitride (Si3N4) has excellent mechanical properties such as high-temperature strength and abrasion resistance, as well as heat resistance, low thermal expansion, thermal shock resistance, and corrosion resistance against metals such as Al and Ag. Therefore, silicon nitride sintered bodies are used as structural materials for gas turbines, engines, steelmaking machines, etc., and as materials resistant to melting damage by molten metals. In addition, because of its excellent electrical insulation properties, it is used as an electronic component material for circuit boards, etc., and as an electrical insulating material.
[0003] In recent years, semiconductor elements that generate a large amount of heat, such as high-frequency transistors and power semiconductors, have become increasingly popular. Materials for semiconductor elements that generate a large amount of heat must have not only electrical insulation but also excellent heat dissipation properties, so there is an increasing demand for ceramic substrates that exhibit high resistivity and high thermal conductivity. Traditionally, aluminum nitride (AlN) has been widely used as a material for ceramic substrates.
[0004] Aluminum nitride has excellent electrical insulation and thermal conductivity, but low mechanical strength and fracture toughness. When an aluminum nitride substrate is fastened during assembly of a circuit board unit, it is prone to cracking. In addition, because the thermal expansion coefficient of aluminum nitride is significantly different from that of silicon, when silicon semiconductor elements are mounted on an aluminum nitride substrate, cracks and breakage easily occur due to thermal expansion and contraction.
[0005] Currently, silicon nitride substrates are being used in place of aluminum nitride substrates, which have problems with mounting reliability. Silicon nitride substrates are sintered bodies of silicon nitride, and are formed from sintered silicon nitride and grain boundary phases derived from sintering aids. Silicon nitride has a lower thermal conductivity than aluminum nitride, but its thermal expansion coefficient is close to that of silicon, and it forms sintered bodies with excellent mechanical strength, fracture toughness, and thermal fatigue resistance.
[0006] Silicon nitride has a stable crystal structure that is strongly bonded by covalent bonds, and is therefore characterized by its excellent heat resistance and high hardness. There are two main crystal structures of silicon nitride: α type and β type. α type is a low-temperature phase of the trigonal crystal system that exists at temperatures lower than around 1400°C. β type is a high-temperature phase of the hexagonal crystal system that is formed by a phase transition from α type at temperatures between 1400°C and 1600°C.
[0007] A known method for producing a silicon nitride sintered body is to sinter silicon nitride powder in a nitrogen gas atmosphere with the addition of a sintering aid. Silicon nitride is a non-oxide, has strong covalent bonds, and is difficult to sinter densely. For this reason, sintering aids such as aluminum oxide, yttrium oxide, and magnesium oxide are added during heat treatment.
[0008] The raw material for sintered bodies produced by self-sintering is mainly α-type silicon nitride powder. α-type silicon nitride undergoes a phase transition to β-type columnar crystals, improving the mechanical properties of the sintered body. Sintered bodies produced by self-sintering are generally known to have excellent mechanical strength, including bending strength. Sintered bodies produced by self-sintering have a thermal conductivity close to 100 W / (m K).
[0009] In addition, a method of manufacturing silicon nitride sintered bodies is known in which silicon powder is subjected to reactive sintering and post-sintering in a nitrogen gas atmosphere. Sintered bodies produced by reactive sintering are expected to have higher thermal conductivity, but the volume of the sintered body changes due to the nitriding reaction of silicon. During reactive sintering, volume expansion due to the nitriding reaction and volume contraction due to sintering occur, making it difficult to mold the body into a near-net shape. Measures are also required to prevent deformations such as warping, cracks, and breakage. The term near-net shape refers to a finished product that is close in size and shape to the finished product, to the extent that secondary processing is not required.
[0010] Patent Document 1 describes a silicon nitride sintered body produced by reactive sintering. This sintered body is produced by a method in which a raw material containing mixed metal silicon of 80% to 95% by weight of coarse metal silicon powder having an average particle size of 10 μm to 30 μm and 5% to 20% by weight of fine metal silicon powder having an average particle size of 1 μm to 10 μm is heated to a temperature of 1390° C. to 1500° C. in a nitrogen atmosphere.
[0011] Patent Document 2 describes a silicon nitride sintered body produced by self-sintering using normal pressure sintering or gas pressure sintering. As the raw material, silicon nitride powder is used that has a specific surface area of 5 m2 / g or more and 20 m2 / g or less, a ratio of β-type silicon nitride of 70 mass% or more, D50 of 0.5 μm or more and 3 μm or less, D90 of 3 μm or more and 6 μm or less, an iron content of 200 ppm or less, an aluminum content of 200 ppm or less, a total content of metal impurities other than iron and aluminum of 200 ppm or less, a crystallite diameter DC of β-type silicon nitride of 60 nm or more, a ratio DBET / DC (nm / nm) of the specific surface area equivalent diameter DBET to the crystallite diameter DC of 3 or less, and a crystal distortion of β-type silicon nitride of 1.5 × 10-4 or less.
[0012] Patent Document 3 describes a silicon nitride sintered body by self-sintering. The sintered body has silicon nitride particles and a grain boundary phase containing Mg and at least one rare earth element, the ratio (RExOy / MgO) of Mg and rare earth element (RE) converted into oxide is in the range of 0.05 to 5, the average long axis length L of silicon nitride particles present in an arbitrarily set 20×20 μm area on the processed surface is 5.0 μm or less, the average ratio (L / S) of the long axis length L to the short axis length S is 5 or less, the area ratio of pores each having an area of 0.01 μm2 or more is 0.01% to 5% in an arbitrarily set 300×300 μm area on the processed surface, the average value of the distance between the centers of gravity of the most adjacent pores among the pores is 5 μm or more, and the coefficient of variation of the distance between the centers of gravity is 1.5 or less. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] Japanese Patent Application Publication No. 7-309669 [Patent Document 2] International Publication No. 2018 / 110564 [Patent Document 3] JP 2014-073945 A Summary of the Invention [Problem to be solved by the invention]
[0014] As a manufacturing method for silicon nitride sintered bodies, a method using reactive sintering is expected to achieve high thermal conductivity and fracture toughness. In order to obtain higher thermal conductivity in a manufacturing process using reactive sintering, it is important to reduce the voids in the sintered body and increase the packing rate of silicon nitride. However, there is room for improvement in conventional technology with regard to increasing the packing rate.
[0015] The raw material used in Patent Document 1 has a two-particle distribution in which two types of metal silicon powder are mixed, and therefore the particle size difference between the coarse powder and the fine powder may be small, or the particle size frequency distribution may have an extremely two-peak shape. In such cases, the filling property of silicon may be poor, voids of a certain size or larger may be easily formed, or the size and distribution of the voids may vary widely, which may increase the effect of volume expansion accompanying the nitriding reaction.
[0016] In addition, in the case of self-sintering as described in Patent Documents 2 and 3, glass phases, grain boundaries, and voids are easily formed, which is an obstacle to improving thermal conductivity. In general, a method of increasing the packing rate of a sintered body can be considered as a method of increasing the amount of sintering aid added. However, if the amount of sintering aid is increased, the amount of glass phases with low thermal conductivity in the sintered body increases, which may actually decrease the thermal conductivity of the sintered body.
[0017] In addition, in the case of a manufacturing process using reactive sintering, a too high filling rate before the nitriding reaction is also a problem. The silicon that constitutes the precursor of reactive sintering expands in volume with the nitriding reaction. Therefore, if the filling rate of silicon in the precursor is too high, the volume expansion accompanying the nitriding reaction causes large deformation and excessive stress, resulting in poor appearance such as warping, cracks, breakage, poor molding accuracy, etc.
[0018] In particular, when the filling rate of silicon in the precursor is about 82 volume % or more, the volume expansion exceeds the volume of the voids, causing significant defects and failures. In Patent Document 1, reactive sintering is performed, but the filling rate and porosity of the precursor are not clear, and the problem of such volume expansion is not fully considered.
[0019] Therefore, an object of the present invention is to provide a silicon nitride green sheet and a silicon nitride substrate which can provide a silicon nitride sintered body having high thermal conductivity with little appearance defects or molding precision defects. [Means for solving the problem]
[0020] In order to solve the above problems, the green sheet for silicon nitride according to the present invention is used as a precursor for a sintered body of silicon nitride, and is a green sheet for silicon nitride containing silicon, a sintering aid, and a binder, wherein the filling rate of the silicon is 59 volume % or more and 80 volume % or less, and the thickness is 0.1 mm or more and 1 mm or less. Effect of the Invention
[0021] According to the present invention, it is possible to provide a silicon nitride green sheet and a silicon nitride substrate which can provide a silicon nitride sintered body having high thermal conductivity with little appearance defects or molding precision defects. [Brief description of the drawings]
[0022] [Figure 1] FIG. 2 is a flow diagram showing a method for producing a silicon nitride green sheet according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram showing the relationship between the particle size and the filling rate of silicon in a silicon nitride green sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, a silicon nitride green sheet according to one embodiment of the present invention and a method for producing the same will be described with reference to the drawings.
[0024] The silicon nitride green sheet according to this embodiment is used as a precursor for producing a silicon nitride sintered body by reactive sintering. The silicon nitride green sheet contains powdered silicon (Si) and a sintering aid, and may contain a binder as necessary.
[0025] Silicon nitride sintered bodies are obtained by reactive sintering of molded powdered silicon together with a sintering aid in a nitrogen gas atmosphere. When silicon (Si) is heat-treated at high temperatures of about 1300°C or higher in a nitrogen gas atmosphere, it becomes silicon nitride (Si3N4) through a nitriding reaction. The silicon nitride particles are sintered together to obtain a silicon nitride sintered body.
[0026] In this specification, the green sheet for silicon nitride is a sheet-like molded body composed of powdered silicon and a sintering aid, and refers to a precursor before silicon undergoes a nitriding reaction. The green sheet for silicon nitride is in the form of a sheet having a thickness smaller than its width and length, but the width, length and thickness of the sheet are not particularly limited.
[0027] The silicon nitride green sheet according to this embodiment has a silicon filling rate of 59% by volume or more and 80% by volume or less in the sheet, with the remainder being mainly composed of a small amount of sintering aid, a small amount of binder, and voids.
[0028] When silicon particles become silicon nitride through a nitriding reaction, the volume calculated from the unit lattice expands by about 1.22 times. By setting the silicon filling rate in the sheet to between 59 volume% and 80 volume%, the filling rate of silicon nitride after the nitriding reaction can be increased, resulting in the desirable effects described below.
[0029] In order to obtain a high thermal conductivity, it is preferable that the silicon nitride sintered body has a high silicon nitride packing rate. Therefore, it is preferable that the silicon nitride green sheet, which is the precursor of the sintered body, also has a high silicon packing rate. According to calculations using a packing model, if the packing rate of silicon particles is 59 volume % or more, silicon nitride particles are easily bonded during the nitriding reaction and sintering reaction. As a result, it is possible to obtain a high thermal conductivity.
[0030] If the silicon filling rate in the silicon nitride green sheet is higher than 80% by volume, the silicon nitride filling rate after the nitriding reaction will be close to 100% by volume, leaving insufficient space for the volume expansion that accompanies the nitriding reaction. In such cases, the sintered body will suffer from significant deformation and stress due to volume expansion exceeding the volume contraction caused by sintering and restrictions on particle rearrangement. In contrast, if a void of about 2% by volume or more is provided, the volume expansion and rearrangement of particles will be permitted, and the deformation and stress can be alleviated, even if volume expansion occurs due to the nitriding reaction.
[0031] The filling rate of silicon in the green sheet is at least 59% by volume, but from the viewpoint of increasing the thermal conductivity of the sintered body, it is preferably 65% by volume or more, more preferably 70% by volume or more, and even more preferably 75% by volume or more. It is also at least 80% by volume or less, but can be 75% by volume or less, 70% by volume or less, 65% by volume or less, etc., depending on the application and required performance of the sintered body.
[0032] Defects and defects that occur in sintered bodies are due to volume expansion accompanying the nitriding reaction, thermal expansion due to heating during heat treatment, and thermal contraction due to cooling after heat treatment. Specific examples of defects and defects include cracks, breaks, and appearance defects such as warping that are problematic in applications such as printed circuit boards, as well as poor molding accuracy in molding to near net shapes and target dimensions. These defects and defects can be reduced by lowering the silicon filling rate to ensure voids in the sintered body.
[0033] In the silicon nitride green sheet of this embodiment, when the particle sizes corresponding to 10%, 50% and 90% cumulative undersieve volume fractions in the volume-based cumulative particle size distribution of silicon are D10, D50 and D90, respectively, the ratio of D10 to D90 (D10 / D90) is greater than 0 and equal to or less than 0.15, and the ratio of D50 to D90 (D50 / D90) is equal to or less than 0.4.
[0034] When D50 / D90 is 0.4 or less, small particles (particles of D10 or less) and medium particles (particles of D10 or more and D50 or less), which account for 50 volume% of the total silicon powder in the sheet, are sufficiently smaller than the large particles (particles of D90 or more), which account for 10 volume% of the total, so that a large amount of small and medium particles can be filled into the gaps between the large particles.
[0035] Furthermore, when D10 / D90 is 0.15 or less, small particles (particles of D10 or less), which account for 10 volume% of the total silicon powder in the sheet, are sufficiently smaller than large particles (particles of D90 or more), which account for 10 volume% of the total, and medium particles (particles of D10 or more and D50 or less), which account for 40 volume% of the total, etc., so that a large amount of small particles can be filled into the gaps between the large and medium particles.
[0036] Therefore, by using silicon that satisfies the above-mentioned D10 / D90 and D50 / D90 conditions, a sufficient number of medium particles can be arranged closely around the large particles, and a sufficient number of small particles can be arranged closely around the medium particles. In addition, the D50 / D90 condition suppresses the size of the voids, and the uniformity of the size and distribution is increased, and the space for volume expansion is dispersedly secured, so that the green sheet for silicon nitride can be obtained that is easy to form uniform bonds between particles due to nitriding reaction and sintering, has a filling rate of silicon in the range of 59 volume % to 80 volume %, and is less likely to cause deformation or stress during reaction sintering.
[0037] D10 / D90 is preferably 0.01 or more, more preferably 0.03 or more. When D10 / D90 is 0.03 or more, the ratio of silicon with an extremely small particle size is low, and the surface area of the powder as a whole is small, so that the amount of binder used can be reduced. D50 / D90 is greater than D10 / D90 of the powder and is 0.4 or less.
[0038] The D50 of the silicon powder in the silicon nitride green sheet is preferably 0.5 μm or more and 20 μm or less. If the D50 is less than 0.5 μm, the amount of binder is small relative to the total specific surface area of the powder, and the mechanical strength of the sheet is low. If the D50 exceeds 20 μm, the surface of the silicon nitride green sheet becomes uneven and the nitriding reaction rate slows down. On the other hand, if the D50 is 0.5 μm or more and 20 μm or less, the surface of the silicon nitride green sheet can be smoothed and the nitriding reaction rate can be increased.
[0039] The D50 of the silicon powder in the silicon nitride green sheet is preferably 0.8 μm or more from the viewpoint of obtaining high strength while suppressing the amount of binder. Also, from the viewpoint of smoothing the surface of the silicon nitride green sheet and accelerating the nitriding reaction rate, it is preferably 10 μm or less, more preferably 4 μm or less, and even more preferably 3 μm or less. When it is 4 μm or less, sufficient smoothness is obtained and the nitriding reaction time can be shortened. When it is 0.8 μm or more and 3 μm or less, high strength can be obtained with a small amount of binder, and a surface with less unevenness can also be obtained. When it is 0.8 μm or more and 2 μm or less, in addition to high strength and smoothness, a higher filling rate can be obtained.
[0040] The particle size and particle size distribution of silicon can be measured using a laser diffraction / scattering type particle size distribution measuring device. The particle size and particle size distribution of silicon in the silicon nitride green sheet can be determined by dissolving the silicon nitride green sheet in a solvent such as alcohol, drying to remove the solvent, and separating and measuring the silicon in the resulting powder based on specific gravity, or by observing any cross section of the silicon nitride green sheet with an electron microscope to collect data such as the circle equivalent diameter of silicon particles.
[0041] The porosity of silicon nitride green sheet can be determined by observation with a scanning electron microscope (SEM). An arbitrary cross section of the silicon nitride green sheet is cut out, and the cross section is photographed with an SEM to obtain an SEM image. The SEM image is then processed using binarization or ternarization, and the area ratio of voids per unit area is calculated, assuming that low-density areas in the image are voids that are free of silicon or sintering aids. SEM images are taken at a magnification of 500x to 1000x, for multiple cross sections and microscope fields.
[0042] The number of cross sections for which SEM images are taken is preferably 2 or more, and more preferably 5 or more, in order to reduce variation due to measurement errors. The average void area ratio is calculated based on a large number of SEM images, and when the variation in the average value becomes sufficiently small with increasing number of images, the average area ratio is taken as the void ratio of the silicon nitride green sheet. When the amount of sintering aid and binder in the sheet is small, it can be considered that silicon filling rate [%] = 100 - void ratio [%].
[0043] As the sintering aid, it is preferable to use a compound containing one or more elements selected from the group consisting of magnesium (Mg), yttrium (Y), and rare earth elements (RE). Examples of compounds containing these elements include oxides, nitrides, and silicides. The sintering aid may contain one or more of these elements.
[0044] The rare earth elements include the lanthanides lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu).
[0045] Mg, Y and rare earth elements have low solid solubility in silicon nitride and are unlikely to change the crystal structure or chemical composition, so they are effective in increasing the thermal conductivity of silicon nitride itself. In particular, Mg and Y are effective in densifying the sintered body to obtain high thermal conductivity. Magnesium oxide (MgO) and yttrium oxide (Y2O3) are preferred compounds containing Mg and Y.
[0046] As the rare earth element, one or more elements selected from the group consisting of La, Ce, Gd, Dy and Yb are particularly preferred. The sintering aid containing these elements can promote sintering while suppressing the temperature and pressure, thereby reducing the cost of heat treatment.
[0047] When the composition of the sintering aid contains La, Y, Gd or Yb and Mg, where the mixed weight of the rare earth elements converted into oxides is RExOy and the mixed weight of magnesium converted into oxide is MgO, it is preferable that RExOy / MgO>1. If the weight ratio of these rare earth elements to Mg is increased, fine particles derived from the sintering aid are more likely to be formed during heat treatment. This is because these rare earth elements are less likely to form a solid solution in silicon nitride than Mg.
[0048] The amount of the sintering aid, calculated as oxide, is preferably 1% by mass or more, more preferably 2% by mass or more, based on 100% by mass of the total of silicon and sintering aid. Also, it is preferably 15% by mass or less, more preferably 10% by mass or less. With such an amount, it is possible to promote sintering of silicon nitride and high purification within the particles, while suppressing the formation of a glass phase with low thermal conductivity.
[0049] The thickness of the silicon nitride green sheet is preferably 0.1 mm or more and 1 mm or less, and more preferably 0.1 mm or more and 0.5 mm or less. With such a thickness, a thin silicon nitride sintered body can be produced. The silicon nitride green sheet of such a thickness may be obtained by pressing after drying during the manufacturing process, or may be obtained without pressing after drying. If the thickness is reduced to 0.5 mm or less by pressing, a higher thermal conductivity can be obtained.
[0050] According to the above-mentioned silicon nitride green sheet, silicon that satisfies the above-mentioned conditions of D10 / D90 and D50 / D90 is used, so that a precursor can be obtained in which the filling rate of silicon is in the range of 59% by volume to 80% by volume, and the space for volume expansion accompanying the nitriding reaction is dispersedly secured for the volume expansion. It is also possible to secure a high filling rate close to 80% by volume at the stage of the precursor of the silicon nitride sintered body, and since the bonds between the particles are easily formed uniformly by the nitriding reaction and sintering, a dense silicon nitride sintered body can be obtained. Therefore, when used in a manufacturing process by reactive sintering, a silicon nitride sintered body that has high thermal conductivity and has few appearance defects such as warping, cracks, breaks, and molding accuracy defects can be obtained.
[0051] Next, a method for manufacturing the silicon nitride green sheet having a filling rate of silicon within a predetermined range will be described. In the following description, a manufacturing method in which raw material powders are wet-mixed and finally dried will be exemplified together with a heat treatment method.
[0052] FIG. 1 is a flow diagram showing a method for producing a silicon nitride green sheet according to an embodiment of the present invention. 1, the method for producing a silicon nitride green sheet according to this embodiment includes a particle size adjusting step S10, a mixing step S20, a coating step S30, and a drying step S40. Through these steps, a silicon nitride green sheet having a silicon filling rate of 59% by volume or more and 80% by volume or less, which serves as a precursor of a silicon nitride sintered body, can be obtained.
[0053] The silicon nitride sintered body is obtained as a silicon nitride substrate, which is a plate-shaped sintered body, by using the silicon nitride green sheet as a precursor and passing through a heat treatment step S50. The silicon nitride substrate can be used for applications such as printed circuit boards.
[0054] In the particle size adjustment step S10, the particle size distribution of the powdered silicon used as the raw material of the silicon nitride green sheet is adjusted so that the filling rate of silicon in the silicon nitride green sheet is within a predetermined range. The particle size distribution can be adjusted by mixing the powders together so that D10 / D90 is greater than 0 and 0.15 or less, and D50 / D90 is 0.4 or less.
[0055] As the silicon powder to be mixed, it is preferable to use multiple types of classified powders with different median diameters (D50) and mode diameters. The powdered silicon used as the raw material for the silicon nitride green sheet is preferably adjusted to have a D50 of 0.5 μm or more and 20 μm or less.
[0056] For example, a method can be used in which 100% by weight of large particle powder with a median diameter of 0.5 μm or more and 20 μm or less is used to add 10% by weight or more and 50% by weight or less of small particle powder with a median diameter of approximately 0.15 to 0.4 times that of the large particles; or a method can be used in which 100% by weight of large particle powder with a median diameter of 0.5 μm or more and 20 μm or less is used to add 40% by weight or less of medium particle powder with a mode diameter of approximately 0.4 times or less and 10% by weight or less of small particle powder with a mode diameter of approximately 0.15 times or less.
[0057] In the mixing step S20, powdered silicon and sintering aid are mixed in a dispersion medium to prepare a slurry. Silicon with a controlled particle size distribution and sintering aid are weighed to a predetermined mixing ratio, and a binder or dispersant is added as necessary, and wet-mixed in the dispersion medium. Wet mixing can suppress the inclusion of gas components without significantly affecting the particle size distribution, and can obtain the dispersion effect of the powder and the dissociation effect of aggregated particles.
[0058] From the viewpoint of dispersibility in silicon, it is preferable to use a powder of a sintering aid having a particle size smaller than D50 of silicon.
[0059] As the binder, any suitable type can be used, such as acrylic resins such as polyacrylic acid and polyacrylic acid ester, cellulose resins such as methyl cellulose and ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, etc., as long as they are pyrolyzed at low temperatures and do not leave behind a large amount of ash, carbon, etc. Use of a binder can prevent particles from falling off from the silicon nitride green sheet after molding, making it easier to handle the sheet.
[0060] Any suitable type of dispersion medium can be used as long as it volatilizes at low temperatures and dissolves the binder added as necessary. When using a water-soluble binder such as polyacrylic acid, lower alcohols such as methanol, ethanol, and butanol can be used. In addition, organic solvents such as hexane, trichloroethylene, and dichloromethane, and water can be used as long as they do not react excessively with silicon or the binder.
[0061] The raw materials can be mixed using an appropriate mixer such as a V-type mixer, a W-type mixer, a Henschel mixer, a ribbon mixer, a screw mixer, a ball mill, a bead mill, a planetary mixer, a high-pressure homogenizer, an ultrasonic homogenizer, or a roll mill.
[0062] In the coating step S30, the slurry is applied onto the substrate to form a coating film containing powdered silicon, a sintering aid, a binder added as necessary, and a dispersion medium. The thickness of the coating film can be appropriately determined depending on the application and required performance of the sintered body. However, from the viewpoint of reducing the unevenness of the surface of the sintered body and the thickness variation within the surface, a thickness of 0.1 mm to 1 mm after drying is preferable.
[0063] As the substrate, any suitable type of material such as a resin film, a resin plate, a metal plate, a ceramic plate, a glass plate, etc. can be used as long as it has a sufficiently high heat resistance temperature relative to the vaporization temperature of the dispersion medium. As the substrate, a resin film is particularly preferred because it can be wound into a roll as a carrier tape. Specific examples of the resin film include polyethylene terephthalate, polyethylene naphthalate, polycarbonate, etc.
[0064] The slurry can be applied by a suitable coating device such as a sheet forming applicator equipped with a doctor blade or the like, a slot die coater, a knife coater, a bar coater, a gravure coater, a spray coater, etc. As the coating device, any of a roll coater, a sheet-fed coater, etc. may be used, and a device for a casting method or an extrusion molding method may also be used.
[0065] In the drying step S40, the slurry coated on the substrate is dried to form a silicon nitride green sheet. The substrate on which the coating film of the slurry is formed is placed in a heating and drying furnace or the like, and the coating film is dried to remove the dispersion medium, leaving powdered silicon and sintering aid on the substrate together with a binder added as necessary, and a silicon nitride green sheet in which the powders are bonded together is obtained.
[0066] The drying temperature and drying time can be appropriately set according to the volatilization temperature of the dispersion medium, within a range that does not cause deterioration of the material. The silicon nitride green sheet obtained after drying may or may not be peeled off from the substrate before the heat treatment. In addition, processing such as cutting and punching may be performed before the heat treatment.
[0067] After drying, the silicon nitride green sheet can be subjected to a pressure treatment in order to adjust the silicon filling rate, porosity, or sheet thickness. By controlling the silicon particle size distribution, the filling rate of silicon in the sheet can be made 59 volume % or more. However, when the silicon filling rate is to be increased or the sheet thickness is to be adjusted, the silicon may be compressed by pressure treatment to densify it. The pressure treatment can be performed using an appropriate pressure device such as an axial press or a roll press.
[0068] In the heat treatment step S50, the silicon nitride green sheet is heat treated in a nitrogen gas atmosphere. When heat treatment is performed at high temperatures, silicon and nitrogen gas gradually react to produce silicon nitride, and a silicon nitride substrate is obtained in which silicon nitride particles are sintered together. The sintering aid melts and volatilizes during the heat treatment, forming an interface of a liquid phase, etc., which becomes a reaction site, on the silicon surface, etc., and after heat treatment, a grain boundary phase containing components derived from the sintering aid is formed in the structure.
[0069] The heat treatment temperature and heat treatment time can be set as appropriate depending on the average particle size of silicon, the type of sintering aid, the mixing ratio of silicon and the sintering aid, etc. When a binder is included, a low-temperature heat treatment for degreasing can be performed before the heat treatment for reactive sintering by the nitriding reaction.
[0070] A preferred heat treatment method is a multi-stage heat treatment including a heat treatment for reactive sintering by a nitriding reaction and a heat treatment for promoting sintering between silicon nitride particles. The reactive sintering can be carried out in a nitrogen gas atmosphere, for example, at 1300°C to 1600°C. The sintering between silicon nitride particles can be carried out in a nitrogen gas atmosphere, for example, at 1720°C to 2000°C.
[0071] These processes make it possible to increase the packing rate of silicon nitride in the sintered body. The remainder in the sintered body is mainly composed of a small amount of grain boundary phase containing components derived from the sintering aid, and voids. It is preferable that the sintered body of silicon nitride has a high β fraction of silicon nitride.
[0072] Silicon nitride substrates can be used as final products for substrate applications without secondary processing. Examples of applications of silicon nitride substrates include printed circuit boards. In particular, they are suitable as materials for high-frequency transistors, power modules such as power semiconductors, and circuit boards for multi-chip modules. They can also be used as heat transfer plates for heat sinks, Peltier elements, Seebeck elements, and the like.
[0073] FIG. 2 is a diagram showing the relationship between the particle size and the packing rate of silicon in a silicon nitride green sheet. In Fig. 2, the horizontal axis indicates the ratio of silicon D10 to D90 (D10 / D90) and the ratio of silicon D50 to D90 (D50 / D90), and the vertical axis indicates the filling rate of silicon in the silicon nitride green sheet. The silicon particle size and filling rate are calculated values. It is assumed that some of the voids are filled with binder.
[0074] The △ plots show the D10 / D90 of silicon obtained when pressure treatment is not applied after drying. The ◯ plots show the D50 / D90 of silicon obtained when pressure treatment is not applied after drying. A1 and A2, B1 and B2, C1 and C2 are each the values for the same silicon nitride green sheet. A, B and C have different particle size distributions.
[0075] The ▲ plot shows the D10 / D90 of silicon obtained when pressure treatment is applied after drying. The ● plot shows the D50 / D90 of silicon obtained when pressure treatment is applied after drying. D1 and D2, E1 and E2, F1 and F2 are each the values for the same silicon nitride green sheet. The DEFs have different particle size distributions.
[0076] As shown in Figure 2, the smaller the particle diameter of silicon's D10 / D90 or D50 / D90, the higher the silicon filling rate. One method for reducing silicon's D10 or D50 is to prepare multiple powders with different median diameters (D50) or mode diameters and add smaller particle powder. In particular, the higher the mixing ratio of powder with a small D50, the greater the change to the smaller particle diameter side.
[0077] As the ▲ and ● plots show, when the silicon is compressed by pressure treatment after drying, the binder and small particles can be moved into the gaps between the silicon particles, resulting in a higher packing rate compared to when pressure treatment is not performed. With pressure treatment, the packing rate of silicon in the sheet can be easily adjusted to about 80 volume%.
[0078] Next, specific examples of silicon nitride green sheets will be described.
[0079] (Examples 1 to 3) Examples 1 to 3 were made from raw materials in which silicon and sintering aid were mixed in a weight ratio of 95:5. Silicon powder with a controlled particle size distribution shown in Table 1 below was used as silicon, YO as sintering aid, polyacrylic acid as binder, and butanol as dispersion medium. The thickness of the silicon nitride green sheet was 0.5 mm. Examples 1 to 3 correspond to C to A in FIG. 2, respectively.
[0080] (Examples 4 to 6) Examples 4 to 6 were made from raw materials in which silicon and a sintering aid were mixed in a weight ratio of 95:5. The silicon was a powder with a controlled particle size distribution as shown in Table 1 below, the sintering aid was a mixture of Y2O3 and MgO in a weight ratio of 2:3, the binder was polyacrylic acid, and the dispersion medium was butanol. The thickness of the silicon nitride green sheet was 0.5 mm. Examples 4 to 6 correspond to C to A in FIG. 2, respectively.
[0081] (Examples 7 to 8) Examples 7 to 8 were produced by using a raw material in which silicon and a sintering aid were mixed in a weight ratio of 95:5, forming a sheet-like coating film, and then applying pressure using a roll press. Silicon was a powder with a controlled particle size distribution as shown in Table 1 below, sintering aid was either Y2O3 alone or a mixture of Y2O3 and MgO in a weight ratio of 2:3, binder was polyacrylic acid, and dispersion medium was butanol. The thickness of the silicon nitride green sheet was 0.5 mm. Examples 7 to 8 correspond to D in FIG. 2, respectively.
[0082] Comparative Example 1 Comparative Example 1 was produced using a raw material in which the silicon particle size distribution of Example 1 was shifted to the larger particle size side. The conditions other than the silicon particle size were the same as those of Example 1.
[0083] Comparative Example 2 Comparative Example 2 was produced using a raw material in which the silicon particle size distribution of Example 4 was shifted to the larger particle size side. The conditions other than the silicon particle size were the same as in Example 4.
[0084] Table 1 shows the composition of the raw material and the manufacturing conditions for the silicon nitride green sheet. Table 2 shows the particle size of the silicon powder used as the raw material, the calculation results of D10 / D90·D10 / D50, and the calculation results of the silicon filling rate.
[0085] [Table 1]
[0086] [Table 2]
[0087] As shown in Tables 1 and 2, in all of the systems of Examples 1 to 3 and Examples 4 to 6, which have different compositions of the sintering aid, the smaller the D10 / D90 or D50 / D90, the higher the silicon filling rate. This result is based on the silicon particles converted into spherical shapes, so the relative size relationship of the particle diameters is important, and it can be said that it is preferable to satisfy the above-mentioned D10 / D90 and D50 / D90 conditions according to the particle diameter range of the silicon suitable as a raw material.
[0088] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible within the scope of the present invention. For example, the present invention is not necessarily limited to having all the configurations of the above embodiment. It is possible to replace a part of the configuration of an embodiment with another configuration, add a part of the configuration of an embodiment to another form, or omit a part of the configuration of an embodiment. [Explanation of symbols]
[0089] S10 Particle size adjustment process S20 Mixing process S30 Coating process S40 Drying process S50 heat treatment process
Claims
1. A silicon nitride green sheet used as a precursor of a silicon nitride sintered body, the green sheet containing silicon, a sintering aid, and a binder, The filling rate of the silicon is 59% by volume or more and 80% by volume or less, A green sheet for silicon nitride having a thickness of 0.1 mm or more and 1 mm or less.
2. 2. The silicon nitride green sheet according to claim 1, A green sheet for silicon nitride, in which the ratio of D10 to D90 (D10 / D90) is greater than 0 and is not greater than 0.15, where D10 and D90 are particle sizes corresponding to 10% and 90% volume fractions in a volume-based cumulative particle size distribution of silicon, respectively.
3. 3. The silicon nitride green sheet according to claim 1, A green sheet for silicon nitride, wherein D50 is a particle diameter corresponding to 50% volume fraction in a volume-based cumulative particle diameter distribution of the silicon, and D50 of the silicon is 0.5 μm or more and 20 μm or less.
4. The silicon nitride green sheet according to any one of claims 1 to 3, A green sheet for silicon nitride, wherein the sintering aid is a powder having a particle diameter smaller than D50 of silicon, where D50 is a particle diameter corresponding to 50% volume fraction in a volume-based cumulative particle diameter distribution of the silicon.
5. 5. A silicon nitride substrate obtained by subjecting the silicon nitride green sheet according to claim 1 to a heat treatment process as a precursor.
Citation Information
Patent Citations
Low heat-conductive silicon nitride sintered body by direct nitriding method having two kinds of particle distribution and its production
JP1995309669A
Reaction-sintered ceramic and its production
JP1997175870A
Method for producing silicon nitride-based ceramic
JP2011195395A
Method for producing silicon nitride substrate
JP2015199657A
Method of manufacturing silicon nitride substrate and silicon nitride substrate
JP2018184333A